Selling Diversity: Immigration, Multiculturalism and Employment Equity - Abu-Laban, Yasmeen; Gabriel, Christina (Broadview Press, 2008)
Since the 1990s, Canadian policy prescriptions for immigration, multiculturalism, and employment equity have equated globalization with global markets. This interpretation has transformed men and women of various ethnic backgrounds into trade-enhancing commodities who must justify their skills and talents in the language of business. This particular neo-liberal reading of globalization and public policy has resulted in a trend the authors call selling diversity. Using gender, race/ethnicity, and class lenses to frame their analysis, the authors review Canadian immigration, multiculturalism, and employment equity policies, including their different historical origins, to illustrate how a preference for selling diversity has emerged in the last decade. In the process they suggest that a commitment to enhance justice in a diverse society and world has been muted. Yet, neo-liberalism is not the only or inevitable option in this era of globalization, and Canadians are engaging in transnational struggles for rights and equality and thereby increasing the interconnectedness between peoples across the globe. Consequently, the emphasis on selling diversity might be challenged.
Keywords: Diversity; Equality; Equity; Immigrants

Building a Better World: An Introduction to Trade Unionism in Canada - Black, Errol; Silver, James (Fernwood, 2008)
Substantially revised and updated, this widely used introductory text emphasizes how values, objectives and activities of unions are shaped in the face of employer resistance and hostile governments. It includes an analysis of why workers form unions; organization and democracy; collective bargaining and grievances; historical development; and gains unions have achieved for their members and all working people. It also examines the challenges created by rapid economic and technological change, the rise of neoliberalism and the increasingly contingent and acialized character of the labour force. --Publisher's description
Keywords: History; Labor Unions

Nation and Society: Readings in Post-Confederation Canadian History, volume 2 - Conrad, Margaret; Finkel, Alvin (Pearson Longman, 2008)
[This textbook] is a balanced collection of the best readings on the history of Canada since Confederation. The readings are separated into five parts: Inventing Canada, 1867-1914; Economy and society in the Industrial Age, 1867-1918; Transitional years, Canada 1919-1945; Reinventing Canada, 1945-1975; and Post-Modern Canada. With 13 new readings, the book will challenge and enlighten students by opening a window to Canada's past and to the ever-evolving examination of Canadian history. --Publisher's description
Keywords: Canada -- History -- 1867- -- Textbooks

Barnacle Love - De Sa, Anthony (Penguin Random House Canada, 2008)
Like Wayson Choy and David Bezmozgis before him, Anthony De Sa captures, in stories brimming with life, the innocent dreams and bitter disappointments of the immigrant experience. At the heart of this collection of intimately linked stories is the relationship between a father and his son. A young fisherman washes up nearly dead on the shores of Newfoundland. It is Manuel Rebelo who has tried to escape the suffocating smallness of his Portuguese village and the crushing weight of his mother’s expectations to build a future for himself in a terra nova. Manuel struggles to shed the traditions of a village frozen in time and to silence the brutal voice of Maria Theresa da Conceicao Rebelo, but embracing the promise of his adopted land is not as simple as he had hoped. Manuel’s son, Antonio, is born into Toronto’s little Portugal, a world of colourful houses and labyrinthine back alleys. In the Rebelo home the Church looms large, men and women inhabit sharply divided space, pigs are slaughtered in the garage, and a family lives in the shadow cast by a father’s failures. Most days Antonio and his friends take to their bikes, pushing the boundaries of their neighbourhood street by street, but when they finally break through to the city beyond they confront dangers of a new sort. With fantastic detail, larger-than-life characters and passionate empathy, Anthony De Sa invites readers into the lives of the Rebelos and finds there both the promise and the disappointment inherent in the choices made by the father and the expectations placed on the son. --Publisher's description
Keywords: Authors, Canadian (English) 21st century; Canadian fiction; Domestic fiction; Fiction; Immigrants; Immigrants Fiction; Newfoundland and Labrador; Newfoundland and Labrador Fiction; Nouvelles; Ontario Toronto; Short stories; Toronto (Ont.) Fiction; short stories

Cultivating Farmworker Rights: Ending the Exploitation of Immigrant and Migrant Farmworkers in BC - Fairey, David; Hanson, Christina; MacInnes, Glen; McLaren, Arlene Tigar; Otero, Gerardo; Thompson, Mark (Canadian Centre for Policy Alternatives, 2008)
A new study of farm work in BC reveals systematic violations of employment standards and health and safety regulations, poor and often dangerous working conditions, and dismal enforcement by government agencies. The study’s authors propose comprehensive policy changes that would ensure farmworkers — most of whom are immigrants and temporary migrants — are no longer relegated to second-class status. “Farmworkers are at the mercy of a complex and confusing system that exploits, threatens and silences them while putting their lives in danger,” says study co-author Arlene McLaren, Professor Emerita of Sociology at Simon Fraser University. The study draws from numerous sources, including interviews with key informants in government and the farm industry, interviews with 53 Indo-Canadian immigrant and Mexican migrant farmworkers, a survey 87 Mexican migrant farmworkers, and a review of better practices in other jurisdictions. The study is part of the Economic Security Project, a joint initiative of the Canadian Centre for Policy Alternatives and Simon Fraser University. --Publisher's description
Keywords: Agricultural laborers; British Columbia; Civil rights; Legal status, laws, etc

Industrial Relations in Canada - Hebdon, Robert; Brown, Travor C. (Nelson Series in Human Resources Management, 2008)
This text presents a hands-on examination of industrial relations balanced in both theoretical and practical coverage, as well as union and labour coverage. Industrial Relations in Canada is grounded in leading research and examines true-to-life issues. Experiential exercises, cases, and collective bargaining simulations bridge the academic content of the text with real-world issues in the field. --Publisher's description of 2011 edition.

Working in Steel: The Early Years in Canada, 1883-1935 - Heron, Craig (Canadian social history series, 2008)
In this indispensable study of Canadian industrialization, Craig Heron examines the huge steel plants that were built at the turn of the twentieth century in Sydney and New Glasgow, Nova Scotia, and Trenton, Hamilton, and Sault Ste. Marie, Ontario. Presenting a stimulating analysis of the Canadian working class in the early twentieth century, Working in Steel emphasizes the importance of changes in the work world for the larger patterns of working-class life. Heron's examination of the impact of new technology in Canada's Second Industrial Revolution challenges the popular notion that mass-production workers lost all skill, power, and pride in the work process. He shifts the explanation of managerial control in these plants from machines to the blunt authoritarianism and shrewd paternalism of corporate management. His discussion of Canada's first steelworkers illuminates the uneven, unpredictable, and conflict-ridden process of technological change in industrial capitalist society. As engaging today as when first published in 1988, Working in Steel remains an essential work in Canadian history. --Pubisher's description
Keywords: Canada; Capitalism; History; Industrial; Working class

One Step Over the Line: Toward a History of Women in the North American Wests - Jameson, Elizabeth; McManus, Sheila (West unbound, 2008)
This eclectic and carefully organized range of essays--from women's history and settler societies to colonialism and borderlands studies--is the first collection of comparative and transnational work on women in the Canadian and U.S. Wests. It explores, expands, and advances the aspects of women's history that cross national borders. Out of the talks presented at the 2002 "Unsettled Pasts: Reconceiving the West through Women's History," Elizabeth Jameson and Sheila McManus have edited a foundational text with a wide, inclusive perspective on our western past. --Publisher's description. Contents: Connecting the women's Wests / Elizabeth Jameson -- Unsettled pasts, unsettling borders: women, Wests, nations / Sheila McManus -- Making connections: gender, race and place in Oregon contry / Susan Armitage -- A transborder family in the Pacific North West: reflecting on race and gender in women's history / Sylvia van Kirk -- Writing women into the history of the North American Wests, one woman at a time / Jean Barman -- "That understanding with nature":region, race, and nation in women's stories from the modern Canadian and American Grasslands West / Molly P. Rozum -- The perils of rural women's history: (a note to storytellers who study the West's unsettled past) / Joan M. Jensen -- The great white mother: maternalism and American Indian child removal in the American West, 1880-1940 / Margaret D. Jacobs -- Pushing physical, racial, and ethnic boundaries: Edith Lucas and public education in British Columbia, 1903-1989 / Helen Raptis -- "Crossing the line": American prostitutes in Western Canada, 1895-1925 / Char Smith -- "Talented and charming strangers from across the line": gendered nationalism. class privilege, and the American woman's club of Calgary / Nora Faires -- Excerpts from Pourin' Down Rain / Cheryl Foggo -- "A union without women is only half organized": Mine Mill, women's auxiliaries, and cold war politics in the North American Wests / Laurie Mercier -- Jailed heroes and kithen heroines: class, gender, and the Medalta Potteries strike in postwar Alberta / Cynthia Loch-Drake -- Gendered steps across the border: teaching the history of women in the American and Canadian Wests / Margaret Walsh -- Latitudes and longitudes: teaching the history of women in the U.S. and Canadian Wests / Mary Murphy.
Keywords: Boundaries; Canada; Canada Boundaries United States; Canada Boundaries United States Congresses; Canada Frontières États-Unis; Canada Frontières États-Unis Congrès; Conference papers and proceedings; Femmes Canada (Ouest) Histoire Congrès; Femmes États-Unis (Ouest) Histoire Congrès; HISTORY General; History; United States; United States Boundaries Canada; United States Boundaries Canada Congresses; West United States; Western Canada; Women; Women Canada, Western History; Women Canada, Western History Congresses; Women West (U.S.) History; Women West (U.S.) History Congresses; États-Unis Frontières Canada; États-Unis Frontières Canada Congrès

Management of Occupational Health and Safety - Kelloway, E. Kevin; Francis, Lori D (Thomson Nelson, 2008)
Based on the premise that occupational health and safety concerns can directly impact an organizations productivity and profitability, this 4th Canadian edition of Management of Occupational Health and Safety helps Human Resource Managers understand health and safety issues, legislation and programs. This edition also provides an up-to-date review of current issues, and methodologies affecting the occupational health and safety standards and practices of Canadian organizations. --Publisher's description
Keywords: Canada; Health and Safety

Mining Town Crisis: Globalization, Labour, and Resistance in Sudbury - Leadbeater, David (Fernwood, 2008)
Sudbury is the largest hardrock mining centre in North America and among the largest in the world. Given the enormous mineral wealth that exists in the Sudbury Basin, one might think that prosperity would abound and that cultural, educational, health and social-welfare institutions would be of the highest order, existing within a well-maintained and attractive physical infrastructure. But this is not the Sudbury that people know. This book explores key aspects of Sudbury’s economic, health and social conditions. It analyzes how globalization and corporate power in a hinterland mining town have impacted on working people, how and why resistance has emerged and why alternative directions are needed. While Sudbury is the focus of this book, the Sudbury experience offers important lessons for other mining and resource communities. --Publisher's description.
Keywords: History / Canada / General; Political Science / Globalization; Political Science / Labor & Industrial Relations

Makúk: A New History of Aboriginal-White Relations - Lutz, John S. (UBC Press, 2008)
The history of Aboriginal-settler interactions in Canada continues to haunt the national imagination. Despite billions of dollars spent on the "Indian problem," Aboriginal people remain the poorest in the country. Because the stereotype of the "lazy Indian" is never far from the surface, many Canadians wonder if the problem lay with "Indians" themselves. John Lutz traces Aboriginal people's involvement in the new economy, and their displacement from it, from the first arrival of Europeans to the 1970s. Drawing upon oral histories, manuscripts, newspaper accounts, biographies, and statistical analysis, Lutz shows that Aboriginal people flocked to the workforce and prospered in the late 19th century. The roots of today's wide-spread unemployment and "welfare dependency" date only from the 1950s, when deliberate and inadvertent policy choices--what Lutz terms the "white problem"--drove Aboriginal people out of the capitalist, wage, and subsistence economies, offering them welfare as "compensation." -- Publisher's description. Contents: Introduction: Molasses stick legs -- Pomo Wawa: the other jargon -- Making the lazy Indian -- The Lekwungen -- The Tsilhqot'in -- Outside history: labourers of the aboriginal province -- The white problem -- Prestige to welfare: remaking the moditional economy -- Conclusion: the outer edge of probability, 1970-2007 -- Postscript: subordination without subjugation.
Keywords: British Columbia; Commerce; Commerce. Indians of North America; Economic conditions. Indians of North America; Employment; Employment. Indians of North America; Government relations. Indians of North America; Government relations. Whites; History. Indians of North America; Whites

Reasoning Otherwise: Leftists and the People's Enlightenment in Canada, 1890-1920 - McKay, Ian (Between the Lines, 2008)
In Reasoning Otherwise, author Ian McKay returns to the concepts and methods of 'reconnaissance' first outlined in Rebels, Reds, Radicals to examine the people and events that led to the rise of the left in Canada from 1890 to 1920. Reasoning Otherwise highlights how a new way of looking at the world based on theories of evolution transformed struggles around class, religion, gender, and race, and culminates in a new interpretation of the Winnipeg General Strike of 1919. As McKay demonstrated in Rebels, Reds, Radicals, the Canadian left is alive and flourishing, and has shaped the Canadian experience in subtle and powerful ways. Reasoning Otherwise continues this tradition of offering important new insight into the deep roots of leftism in Canada. --Publisher's description
Keywords: History; Politics and government; Right and left (Political science); Socialism

Working Girls in the West: Representations of Wage-Earning Women - McMaster, Lindsey (UBC Press, 2008)
As the twentieth century got underway in Canada, young women who entered the paid workforce became the focus of intense public debate. Young wage-earning women - "working girls"--Embodied all that was unnerving and unnatural about modern times: the disintegration of the family, the independence of women, and the unwholesomeness of city life. These anxieties were amplified in the West. Long after eastern Canada was considered settled and urbanized, the West continued to be represented as a frontier where the idea of the region as a society in the making added resonance to the idea of the working girl as social pioneer." "Using an interpretive approach that centres on literary representation, Lindsey McMaster takes a fresh look at the working heroine of western Canadian literature alongside social documents and newspaper accounts of her real-life counterparts. Working Girls in the West heightens our understanding of a figure that fired the imagination of writers and observers at the turn of the last century." --Publisher's description. Contents: Working women in the west at the turn of the century --The urban working girl in turn-of-the-century Canadian literature -- White slaves, prostitutes, and delinquents -- Girls on strike -- White working girls and the mixed-race workplace -- Conclusion: Just girls.

The Impossibilists: A Brief Profile of the Socialist Party of Canada - Newell, Peter E. (Athena, 2008)
Formed in January 1905, the Socialist Party of Canada's anti- reformist, anti-statist revolutionary platform led to ideological disputes with rival socialist groups and even arguments within the Party itself over what it stood for. Peter E Newell's absorbing and thorough account of the life and times of the Socialist Party of Canada charts the Party's pre-history in the 1890s, when the availability of translations of the works of Marx and Engels fuelled the radicalism of such figures as Daniel De Leon. It also covers the early years of the twentieth century when, with the merger of like-minded Provincial socialist parties, the SPC was founded. In the present day the party remains a beacon for socialists worldwide for its refusal to compromise its passions and beliefs. --Publisher's description
Keywords: Socialist Party of Canada

Solidarity First: Canadian Workers and Social Cohesion - O'Brien, Robert (UBC Press, 2008)
As working people’s lives become increasingly fragmented, competitive, and unequal, debates about social cohesion capture the unease of contemporary society over growing economic restructuring. Solidarity First examines the concept and practice of social cohesion in terms of its impact on, and significance for, workers in Canada. Contributors examine how social cohesion functions on multiple levels. They challenge standard approaches by highlighting the experiences of women and non-Canadians. They investigate attempts by Toyota and Magna to construct corporate forms of cohesion and efforts by a local community to forge cohesion via the new cultural economy. And they explore the relationship between cohesion in Canada and the international environment. Critically examining the issue from the ground up, Solidarity First concludes that reinvigorated worker solidarity is a prerequisite to a more worker-friendly form of social cohesion. It will be of interest to students and scholars in the fields of public policy, political science, sociology, and labour studies. --Publisher's description
Keywords: Economic conditions; Employees; Social conditions; Social integration; Social participation; Social values; Solidarity; Working class

Labouring Canada: Class, Gender, and Race in Canadian Working-Class History - Palmer, Bryan D.; Sangster, Joan (Oxford University Press, 2008)
This text is a collection of classic and contemporary articles exploring the nature of work in Canadian history from the late eighteenth century to the current day. Class relations and labour form the core of the volume, but attention will also be paid to the state and its relations with workers both formal and informal. The volume is designed as a core text for classes in Canadian labour/working-class history, taught out of history and labour studies departments. --Publisher's description
Keywords: Canada; History; Labor movement; Social history; Working class

Citizen Docker: Making a New Deal on the Vancouver Waterfront, 1919-1939 - Parnaby, Andrew (Canadian social history series, 2008)
After the First World War, many Canadians were concerned with the possibility of national regeneration. Progressive-minded politicians, academics, church leaders, and social reformers turned increasingly to the state for solutions. Yet, as significant as the state was in articulating and instituting a new morality, outside actors such as employers were active in pursuing reform agendas as well, taking aim at the welfare of the family, citizen, and nation. Citizen Docker considers this trend, focusing on the Vancouver waterfront as a case in point.After the war, waterfront employers embarked on an ambitious program - welfare capitalism - to ease industrial relations, increase the efficiency of the port, and, ultimately, recondition longshoremen themselves. Andrew Parnaby considers these reforms as a microcosm of the process of accommodation between labour and capital that affected Canadian society as a whole in the 1920s and 1930s. By creating a new sense of entitlement among waterfront workers, one that could not be satisfied by employers during the Great Depression, welfare capitalism played an important role in the cultural transformation that took place after the Second World War.Encompassing labour and gender history, aboriginal studies, and the study of state formation, Citizen Docker examines the deep shift in the aspirations of working people, and the implications that shift had on Canadian society in the interwar years and beyond. --Publisher's description. Contents: Introduction: "A good citizen policy" -- Welfare capitalism on the waterfront -- Securing a square deal -- "The best men that ever worked the lumber" -- Heavy lifting -- "From the fury of democracy, good Lord, deliver us!" -- Conclusion: from square deal to new deal. Includes bibliographical references (pages 221-234) and index.

The Dirt: Industrial Disease and Conflict at St. Lawrence, Newfoundland - Rennie, Rick (Fernwood, 2008)
In the cemeteries of St. Lawrence and several neighbouring towns on the south coast of Newfoundland lie the remains of some 200 workers, killed by the dust and radiation that permeated the area’s fluorspar mines. The Dirt chronicles the many forces that created this disaster and shaped the response to it, including the classic ‘jobs or health’ dilemma, the contentious process of determining the nature and extent of industrial disease and the desire of employers to ‘externalize’ the costs of production onto workers and communities. Central to the account is the persistent effort by workers, women in the community and other activists to gain recognition of health hazards in the mines, their effects on workers and to obtain adequate compensation for victims and their families. --Publisher's description.  Contents: Origins of a disaster: working conditions and labour relations in the 1930s -- Protest and retreat: the war years -- Industry revival, increasing hazards and the recognition of sislicosis, 1946-1956 -- More deadly perils: radiation and cancer -- "The truly ghastly total" and the lack of compensation coverage -- Mounting protest, industry closure, and the legacy of the past.
Keywords: Aspect sanitaire; Diseases; Employees; Employees Diseases; Employees Health and hygiene; Fluorspar industry; Health and hygiene; Health and hygiene. Mining; Health aspects; Industrie; Maladies; Mineral dusts; Miners; Newfoundland and Labrador; Newfoundland and Labrador St. Lawrence; Newfoundland and Labrador. Calcium Fluoride; Newfoundland and Labrador. Occupational Diseases; Newfoundland and Labrador. Silicosis; Personnel; St. Lawrence. Fluorite; St. Lawrence. Fluorspar industry; St. Lawrence. Mineral dusts; St. Lawrence. Miners; St. Lawrence. Mineurs; Terre-Neuve-et-Labrador; Toxicologie; Toxicology; Toxicology. Miners

Fighting for Justice and Dignity: The Homer Seguin Story: An Autobiography - Seguin, Homer (Journal Printing, 2008)
Self-published memoir of the Sudbury union activist, Homer Seguin (1934-2013), who championed workplace health and safety to reduce injuries and occupational diseases at mines and other industrial sites. Describes his experiences as a negotiator, president of Local 6500 of the United Steelworkers, and as a USW representative at Elliot Lake, Ontario. Also chronicles the rise of the labour movement in Sudbury and the bitter inter-union battle in the early 1960s between Mine Mill Local 598 and the Steelworkers over the right to represent 20,000 Inco workers.
Keywords: 20th century; Elliot Lake; History. Industrial relations; History. Trade-unions; International Union of Mine, Mill and Smelter Workers. Local 598; Miners; Northeastern Ontario; Occupational health and safety; Seguin, Homer; Sudbury; United Steelworkers of America. Local 6500

Canada's Jews: A People's Journey - Tulchinsky, Gerald J. J (University of Toronto Press, 2008)
The history of the Jewish community in Canada says as much about the development of the nation as it does about the Jewish people. Spurred on by upheavals in Eastern Europe in the late-eighteenth and early-nineteenth centuries, many Jews immigrated to the Dominion of Canada, which was then considered little more than a British satellite state. Over the ensuing decades, as the Canadian Jewish identity was forged, Canada underwent the transformative experience of separating from Britain and distinguishing itself from the United States. In this light, the Canadian Jewish identity was formulated within the parameters of the emerging Canadian national personality." "Canada's Jews is an account of this remarkable story as told by one of the leading authors and historians on the Jewish legacy in Canada. Drawing on his previous work on the subject, Gerald Tulchinsky describes the struggle against antisemitism and the search for a livelihood among the Jewish community. He demonstrates that, far from being a fragment of the Old World, Canadian Jewry grew from a tiny group of transplanted Europeans to a fully articulated, diversified, and dynamic national group that defined itself as Canadian while expressing itself in the varied political and social contexts of the Dominion. --Publisher's description